Implementasi Evaluasi Model Kirkpatrick pada Pelatihan Pemanfaatan Digitalisasi Pada Perpustakaan UPT IAIN Sultan Amai Gorontalo - Ampauleng Zainuddin; Sitti Mania; Muh Nur Akbar Rasyid (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2023)
One of the most widely recognized evaluation models adapted to education is the Kirkpatrick model. However, this model has limitations when used by evaluators, especially in complex higher education environments. In response to the dearth of collective efforts in addressing these limitations, this paper aims to analyze the implementation of the Kirkpatrick evaluation model in the training on the use of digitization in the library of IAIN Sultan Amai Gorontalo. Three themes of limitations were found: a tendency towards using the lower levels of the model; rigor that ignores other important aspects of evaluation; and a lack of evidence on the causal chain between the levels. It is suggested that, when using the Kirkpatrick model in higher education, evaluators should overcome these limitations by considering more appropriate methods, integrating contextual inputs in the evaluation framework, and establishing causal links between the levels